Eddie's boy : a novel - Perry, Thomas, 1947- (Perry, Thomas, 1947- Butcher's Boy, 2020)
"Michael Shaeffer is a retired American businessman, living peacefully in England with his aristocratic wife. But her annual summer party brings strangers to their house, and with them, an attempt on Michael's life. He is immediately thrust into action, luring his lethal pursuers to Australia before venturing into the lion's den-the States-to figure out why the mafia is after him-again-and how to stop them. Eddie's Boy jumps between Michael's current predicament and the past. We glimpse the days before he became the Butcher's Boy, the highly skilled mob hit man who pulled a slaughter job on some double-crossing clients and started a mob war, to his childhood spent apprenticed to Eddie, a seasoned hired assassin. And we watch him pit two prominent mafia families against each other to eliminate his enemies one by one. He's meticulous in his approach, using his senior contact in the Organized Crime Division of the Justice Department for information, but never allowing her to get too close to his trail. But will he be able to escape this new wave of young contract killers, or will the years finally catch up to him? Perry's Edgar Award-winning Butcher's Boy returns in full force in this exhilarating new installment to the beloved series"--